O teorema de Pitágoras: abordagem no cotidiano da educação matemática e suas diversas demonstrações - Silva, Danniel Emanuel Bruno (2014)
This work is about the Pythagorean Theorem and its various statements, addressing its importance and as has been shown in mathematics education. We will present some of the history of Pythagoras, as well as on his theorem, and well see a search on their importance, and how students receive this information. We'll talk a bit about how the textbooks, from elementary school to the middle, deal about it, and finally we will see some statements about this theorem seeking to open a lot more range of options for students and lovers of mathematics teachers. These statements are part of the collection assembled by Loomis, who managed to submit more than three hundred statements of the theorem in a publication of 1940.